Introduction: Old Language(s), New Technologies: Corpus Linguistics and European Languages in the Renaissance, 1400s-1600s - Ciambella, Fabio (Status Quaestionis, 2023)
The six articles included in this monographic section of Status Quaestionis 25 offer interesting perspectives on various levels of linguistic analysis, such as spelling fluctuation, textual pragmatics, morphosyntax, figurative language, etc., and their numerous intersections, using different corpus linguistics tools. Far for being a comprehensive overview of the state of the art on ‘old languages and new technologies’ (which is not the aim of this publication), the case studies presented here provide a glimpse into the potentials offered by corpus linguistics tools when dealing with Renaissance English and Romance languages such as French, Italian, Portuguese and Spanish.